"Express the Real You": Cultural Differences in the Perception of Self-Expression as Authenticity. (September 2014) - Kokkoris, Michail D.; Kühnen, Ulrich
Prior research shows that people feel authentic when they express themselves. In this research, we examined how people from different cultures make inferences about a target person's authenticity based on information about that person's self-expression. Our cultural-fit hypothesis proposes that acts of self-expression enhance perceptions of authenticity when they are congruent with the culturally prevalent self-expression norms. In an experiment with Germans and Chinese reading scenarios and making inferences about a hypothetical person, we found that authenticity judgments were the highest, when the target person's self-expression matched the culturally valued self-expression style—that is, expressing both likes and dislikes in Germany, and expressing only likes but no dislikes in China. Moreover, we found that the interactive effect of self-expression and culture had downstream effects on information processing, such that in the case of counter-cultural self-expression practices participants were more likely to seek information that would compensate for this cultural incongruence.